Pengaruh Promosi Online Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Konsumen Pada Industri Yunita Meubel. - Denisa Anataya Harliyana; Usman Moonti; Agil Bahsoan; Radia Hafid; Sudirman Sudirman (State University of Gorontalo, 2023)
This study aims to determine the effect of online promotion and service quality on consumer purchasing decisions in the Yunita Furniture Industry, Lolak Village, Lolak Sub-district, Bolaang Mongondow Regency. This study uses quantitative research with multiple linear regression statistical analysis, t-test, and F-test. Data collection technique applies questionnaires. The results show that online promotion and service quality have a significant effect on consumer purchasing decisions in the Yunita Furniture Industry, Lolak Village, Lolak Sub-district, Bolaang Mongondow Regency, which is indicated by the value of the regression equation obtained by the price Fcount =4.28 and Frable= (0.95) (1,23) = 91.464, which means Eount F Count F Table according to the test criteria that the regression equation above is significant.